Local influences of geothermal anomalies on permafrost distribution in an active volcanic island (Deception Island, Antarctica) - Goyanes, Gabriel Alejandro (2014)
This study aims at understanding the spatial distribution and characteristics of the frozen and unfrozen terrain in an alluvial fan on Deception Island, which is an active strato-volcano located in the Bransfield Strait (South Shetland Islands) with recent eruptions in 1967, 1969 and 1970. The alluvial fan is dominated by debris-flow, run-off and rock fall processes and permafrost occurs in several parts in the vicinity of anomalous geothermal heat flux. The aim is to assess the ways volcanic activity controls permafrost development and associated geomorphic dynamics using shallow subsurface, surface and air temperature measurements as well as thaw depth and electrical resistivity tomography (ERT) surveys.Results show a temperature increase with depth in the lower part of the fan reaching 13. °C at 0.80. m depth, without the presence of permafrost. The shallow borehole located at this site showed a stable thermal stratification all year-round, with only the upper 0.20. m reacting to meteorological forcing. In the upper part of the alluvial fan and debris cones, c. 100. m from the coast, frozen ground is present at c. 0.70. m depth. There, the shallow borehole shows a good coupling with air temperatures and the thermal regime favours the presence of permafrost. ERT shows the lowest resistivity values in the lower part of the alluvial fan and a highly resistivity zone in the upper sector of the fan and in the debris cones. These large variations in resistivity mark the presence of a saline water wedge from the sea into the fan, reaching frozen ground conditions about 100. m inland. It can be shown that the volcano-hydrothermal activity only inhibits frost development very locally, with frozen ground conditions occurring about 100. m away.